Clinical Improvement According to RAPID3 in Patients With Polymyalgia Rheumatica: A Longitudinal Analysis From Routine Care. Issue 7 (October 2018) - Castrejon, Isabel; Huang, Annie; Everakes, Sarah L.; Nika, Ailda; Sequeira, Winston
Abstract : Supplemental digital content is available in the text.